ANALISIS EFEKTIFITAS DAN KONTRIBUSI PEMUNGUTAN PAJAK REKLAME TERHADAP PENDAPATAN ASLI DAERAH DI PROVINSI DKI JAKARTA TAHUN 2016-2019 - Dewanti, Yopy Ratna (JAB (Jurnal Akuntansi & Bisnis), 2021)
The central government grants autonomy to the regions in the context of equitable development. Regional autonomy is the right, authority and obligation of an autonomous region to regulate and manage its own government affairs and the interests of the local community in accordance with statutory regulations. One of the results of regional autonomy is in the field of taxes. Regional taxes can be seen in regional income which is income derived from the utilization and exploration of the potential owned by the region. One of the local taxes is the advertising tax. Advertisement tax is one of the regional taxes and a source of regional original income that shows a strategic position in terms of regional financing.Effectiveness point of view in 2016, advertising tax revenue was fairly effective (78%) on regional tax revenue at Bapenda DKI Jakarta, and in 2017 it increased to very effective (107.84%), because advertising tax revenue increased and exceeded advertising tax revenue plan that has been determined. In 2018, advertising tax revenue decreased even though it was still at the effective level (88.24%) and in 2019 advertising tax revenue increased to very effective (102.71%) because advertising tax revenue exceeded the predetermined plan. Meanwhile, in terms of the 2016 – 2019 advertising tax revenue contribution, it was very less contributing to regional tax revenue in DKI Jakarta Province, namely in 2016 (2.83%), 2017 (2.61%), 2018 (2.72%) and in 2017. 2019 (2.68%)Keyword: Regional Tax, Advertising Tax, Effectiveness and Contribution.